Study protocol for a randomised controlled trial of CBT vs antipsychotics vs both in 14-18-year-olds: Managing adolescent first episode Psychosis: a feasibility study (MAPS) - Pyle, M; Broome, M; Joyce, E; Maclennan, G; Norrie, J; Freeman, D; Fowler, D; Haddad, P; Shiers, D; Hollis, C; Smith, J; Liew, A; et al. (BioMed Central, 2019)
Background Adolescent-onset psychosis is associated with more severe symptoms and poorer outcomes than adult-onset psychosis. The National Institute for Clinical Excellence (NICE) recommend that adolescents with first episode psychosis (FEP) should be offered a combination of antipsychotic medication (APs), cognitive behavioural therapy (CBT) and family intervention (FI). The evidence for APs in treating psychosis is limited in adolescents compared to adults. Nevertheless, it indicates that APs can reduce overall symptoms in adolescents but may cause more severe side effects, including cardiovascular and metabolic effects, than in adults. CBT and FI can improve outcomes in adults, but there are no studies of psychological interventions (PI) in patients under 18 years old. Given this limited evidence base, NICE made a specific research recommendation for determining the clinical and cost effectiveness of APs versus PI versus both treatments for adolescent FEP. Methods/design The current study aimed to establish the feasibility and acceptability of conducting such a trial by recruiting 14–18-year-olds with a first episode of psychosis into a feasibility prospective randomised open blinded evaluation (PROBE) design, three-arm, randomised controlled trial of APs alone versus PI alone versus a combination of both treatments. We aimed to recruit 90 participants from Early Intervention and Child and Adolescent Mental Health Teams in seven UK sites. APs were prescribed by participants’ usual psychiatrists. PI comprised standardised cognitive behavioural therapy and family intervention sessions. Discussion This is the first study to compare APs to PI in an adolescent population with FEP. Recruitment finished on 31 October 2018. The study faced difficulties with recruitment across most sites due to factors including clinician and service-user treatment preferences. Trial registration Current controlled trial with ISRCTN, ISRCTN80567433. Registered on 27 February 2017.